2017
DOI: 10.3390/electronics6040084
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven ECG Denoising Techniques for Characterising Bipolar Lead Sets along the Left Arm in Wearable Long-Term Heart Rhythm Monitoring

Abstract: Abnormal heart rhythms (arrhythmias) are a major cause of cardiovascular disease and death in Europe. Sudden cardiac death accounts for 50% of cardiac mortality in developed countries; ventricular tachycardia or ventricular fibrillation is the most common underlying arrhythmia. In the ambulatory population, atrial fibrillation is the most common arrhythmia and is associated with an increased risk of stroke and heart failure, particularly in an aging population. Early detection of arrhythmias allows appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Signal noise appears to be more evident when the dry electrodes are used. This is likely due to the interaction between the subjects' skin and the electrode, which in turn creates a rubbing effect [2]. Lead 2, a dry electrode located on the wrist, performed with a median sensitivity of only 0.292 and PPV of 0.191 as presented in Table 2 As for Lead 6, a conductive gel electrode that is also located on the wrist, the median sensitivity achieved was sufficiently larger than that of Lead 2 at 0.411.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal noise appears to be more evident when the dry electrodes are used. This is likely due to the interaction between the subjects' skin and the electrode, which in turn creates a rubbing effect [2]. Lead 2, a dry electrode located on the wrist, performed with a median sensitivity of only 0.292 and PPV of 0.191 as presented in Table 2 As for Lead 6, a conductive gel electrode that is also located on the wrist, the median sensitivity achieved was sufficiently larger than that of Lead 2 at 0.411.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a second order high pass Butterworth filter at 0.5 Hz was used to limit noise due to respiratory artefact. Also, a second order low pass Butterworth filter at 40 Hz was used to limit the bandwidth of the signal and attenuate out band noise and the power-line interference [2].…”
Section: 2mentioning
confidence: 99%
“…Nevertheless, effective denoising techniques for arm-ECG are currently available for the treatment of far-field arm-ECG signals. In previous studies [4], bipolar lead electrodes have been positioned (transversally and axially oriented) on different anatomical locations along the left upper-arm. The study has suggested a transversally-oriented bipolar lead on the upper arm (see Lead-1 definition in Figure 1) as one of the most suitable localizations for ECG signal recovery, and that other locations (Lead-4 and Lead-6) can also provide meaningful ECG information.…”
Section: Bipolar Arm-ecg Signalsmentioning
confidence: 99%
“…In such cases, implantable loop recorders (ILRs) are currently becoming more common and are considered as an important tool by clinicians; however, their use requires costly surgical procedures and carries infection risks [3]. Holter monitors offer high-quality ECG signals for medical diagnosis, but they are typically limited to 24-48 h of continuous use since they require wires that interfere with user's daily activities and skin-adhesive-based electrodes, which may produce patient discomfort after a few days [4] and the adhesive regularly degrades causing electrodes to detach as a result of sweating. Cost-effective, non-invasive, long-term ECG monitoring alternatives for early detection of arrhythmias can have a positive impact on the effectiveness of heart disease treatment, therefore reducing mortality and improving patient's prognosis, particularly in an ageing population [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation